1997
DOI: 10.1136/bmj.314.7089.1238
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of prophylactic or empirical antifungal treatment versus placebo or no treatment in patients with cancer complicated by neutropenia

Abstract: Objective: To assess the impact of handling patients and indicators of individual susceptibility on risk of low back pain in nurses. Design: Prospective cohort study with follow up by repeated self administered questionnaires every three months over two years. Setting: NHS university hospitals trust. Subjects: 961 female nurses who had been free from low back pain for at least one month at the time of completing a baseline questionnaire. Main outcome measures: Incidence of new low back pain during follow up an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
62
1
3

Year Published

1999
1999
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(69 citation statements)
references
References 41 publications
3
62
1
3
Order By: Relevance
“…Application of AmB has not been shown to be beneficial for prophylaxis of IPA in neutropenia [93]. Low dose intravenous cAmB, inhalation of cAmB as well as intranasal cAmB application are well tolerated, but failed to be effective in prevention of IPA [21,82,94,95].…”
Section: Amphotericin Bmentioning
confidence: 99%
“…Application of AmB has not been shown to be beneficial for prophylaxis of IPA in neutropenia [93]. Low dose intravenous cAmB, inhalation of cAmB as well as intranasal cAmB application are well tolerated, but failed to be effective in prevention of IPA [21,82,94,95].…”
Section: Amphotericin Bmentioning
confidence: 99%
“…6 A recent meta-analysis 7 has been conducted of 24 trials in which antifungals were used, either as prophylaxis or as empirical therapy, in patients with cancer complicated by neutropenia. This meta-analysis showed that amphotericin B decreased mortality significantly although the studies were small, as was the difference in the number of deaths.…”
mentioning
confidence: 99%
“…The studies supporting these practices do not always reach a definitive conclusion in terms of modification of existing clinical practice. [1][2][3][4][5][6][7][8][9][10][11][12][13] Therefore, guidelines have been formulated for the prevention of infections following HSCT, 14,15 and have been endorsed by the Centers for Disease Control and Prevention, Infectious Diseases Society of America, and American Society for Blood and Marrow Transplantation. These evidence-based reviews have made weighted recommendations for the use of antimicrobial agents as prophylaxis for bacterial, viral, and fungal pathogens.…”
mentioning
confidence: 99%